Implementasi Evaluasi Ranah Psikomotorik Pada Pembelajaran PAI di SDN Rangperang Daya III - Ayu Ashilah Maulidya; Mad Sa’i (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
Learning evaluation is carried out to obtain information about students' abilities, as well as to measure whether the learning objectives are achieved or not. Learning evaluation covers 3 domains, namely: cognitive (knowledge), affective (values or attitudes), and psychomotor (skills). This research uses qualitative research methods. In this discussion, researchers will discuss the evaluation carried out by PAI teachers at SDN Rangperang Daya III in the psychomotor realm, where teachers not only measure students' knowledge in understanding something but also measure students' abilities in their skills to carry out worship. Psychomotor assessment is characterized by the presence of physical activity and performance skills by students and does not require writing instruments.